2015
DOI: 10.1186/s13293-015-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in autonomic function following maximal exercise

Abstract: BackgroundHeart rate variability (HRV), blood pressure variability, (BPV) and heart rate recovery (HRR) are measures that provide insight regarding autonomic function. Maximal exercise can affect autonomic function, and it is unknown if there are sex differences in autonomic recovery following exercise. Therefore, the purpose of this study was to determine sex differences in several measures of autonomic function and the response following maximal exercise.MethodsSeventy-one (31 males and 40 females) healthy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 45 publications
(51 reference statements)
4
13
2
3
Order By: Relevance
“…It is possible that similarly stressful life milieu of our participants influenced diminished differences in genders. Maximally achieved heart frequencies did not stand in contrast between men and women in our study, which is consistent to previous results (15,17,23).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is possible that similarly stressful life milieu of our participants influenced diminished differences in genders. Maximally achieved heart frequencies did not stand in contrast between men and women in our study, which is consistent to previous results (15,17,23).…”
Section: Discussionsupporting
confidence: 93%
“…Markedly higher lnLF and lnHF values were obtained in males after the Wingate test in compare to women in all menstrual cycle phases. These findings contrast the ones found by authors who reported higher values of HF in women during recovery from the test for maximal oxygen consumption and concluded that women have faster vagal postexercise reactivation (15). In general, HRR is faster after a Wingate test and recovery after an incremental VO2max test sometimes takes several days (42,43), but supra-maximal exercise has a greater impact on autonomic modulation in women.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…For instance, decreased overall HRV, increased sympathetic and/or decreased vagal activity directed to the heart after a myocardial infarction, in hypertension and heart failure are related to increased mortality and morbidity [13][14][15][16] . On the other hand, therapeutic interventions that improve the sympathovagal balance may positively affect prognosis 17, 18 . In addition, HRV studies [19][20][21][22][23] have demonstrated that also pregnancy and menopause in uence the CAP [19][20][21][22][23] . During pregnancy, a high sympathetic modulation directed to heart and vessels has been found in women at the late stage of pregnancy compared to the early stage 24 .…”
Section: Introductionmentioning
confidence: 99%
“…A modulação simpática vasomotora, representada pela BFPAS (EUROPEAN SOCIETY OF CARDIOLOGY; NORTH AMERICAN SOCIETY OF PACING AND ELECTROPHYSIOLOGY, 1996) aumentou ao longo da sessão de exercício e se manteve na sessão controle, demonstrando um efeito do exercício de aumentar essa modulação. Poucos estudos (GOULOPOULOU;FERNHALL;KANALEY, 2009;KAPPUS et al, 2015;NIEMELÄ et al, 2008) investigaram a modulação simpática vasomotora após o exercício aeróbico através da análise espectral e os resultados obtidos foram controversos, com a maioria não verificando nenhum efeito significante (KAPPUS et al, 2015;NIEMELÄ et al, 2008 HEFFERNAN et al, 2007;LACOMBE et al, 2011;LIU et al, 2012). Erro Sist = erro sistemático; Conf = confiabilidade; Conc = concordância; CV = coeficiente de variação; PAS = pressão arterial sistólica; PAD = pressão arterial diastólica; PAM = pressão arterial média; DC = débito cardíaco; RVP = resistência vascular periférica; FC = frequência cardíaca; VS = volume sistólico; ln = logaritmo natural; un = unidades normalizadas; VTR-R = variância total do intervalo R-R; BFR-R = banda de baixa frequência da variabilidade do intervalo R-R; AFR-R = banda de alta frequência da variabilidade do intervalo R-R; BF/AF = razão entre as bandas de baixa e de alta frequência da variabilidade do intervalo R-R; VTPAS = variância total da pressão arterial sistólica (PAS); BFPAS = banda de baixa frequência da variabilidade da PAS; SBR = sensibilidade barorreflexa.…”
Section: Respostas Fisiológicas Ao Exercíciounclassified